Analysis of the mediating effect of invasive ruminative contemplation on the relationship between social support and non-suicidal self-injury behavior in depressed patients - Tang, Mei; Tao, Li; Liu, Jie; Tao, Ni; Peng, Hong; Gu, Jing (Frontiers in Psychiatry, 2026)
ObjectiveTo explore the mediating mechanism of intrusive rumination between social support and non-suicidal self-injury (NSSI) behavior in patients with depression.MethodsPatients with depression admitted to our hospital from September 2023 to February 2024 were selected as the study subjects. A questionnaire survey was conducted using the General Information Questionnaire, Intrusive Rumination Scale, Perceived Social Support Scale, and Ottawa Self-Injury Inventory (OSI). Pearson correlation analysis and structural equation modeling (SEM) were used to test the mediating effect.ResultsThe scores for intrusive rumination, total social support, and NSSI behavior in 120 depressed patients were (15.71 ± 2.13), (47.85 ± 4.69), and (16.35 ± 2.65), respectively. NSSI behavior was negatively correlated with the total social support score and its three dimensions (P< 0.05), and positively correlated with the total intrusive rumination score (P< 0.05). Intrusive rumination showed a mediating effect of 27.40% between social support and NSSI behavior.ConclusionSocial support can influence NSSI behavior in depressed patients by regulating intrusive rumination. It is crucial to emphasize the assessment of intrusive rumination in clinical practice to reduce the occurrence of NSSI behavior.